Predictors of antimicrobial resistance in the respiratory intensive care unit of Alexandria Main University Hospital - Mohamed S. Eltarhony (The Egyptian Journal of Bronchology)
Abstract Background Antimicrobial resistance (AMR) is a growing global health concern, particularly in intensive care units (ICUs), where critically ill patients are at increased risk of infections caused by multidrug-resistant organisms (MDROs). In the respiratory ICU (RICU), the frequent use of invasive procedures and broad-spectrum antibiotics exacerbates this challenge; thus, identifying predictors of resistance is essential to guide effective antimicrobial stewardship and improve patient outcomes. Objectives This study aimed to identify predictors of antimicrobial resistance among patients admitted to the RICU, with the goal of informing early intervention strategies and optimizing patient management. Methods This prospective observational study included patients admitted to the RICU between October and December 2024. Data were collected on demographics, comorbidities, use of invasive devices, prior antibiotic exposure, ICU length of stay, and microbiological culture results. Results Smoking, comorbidities, and immunosuppression emerged as the strongest independent predictors of AMR. Prolonged ICU stay and mechanical ventilation were associated with resistance in univariate analysis. Conclusion Recognizing key predictors of antimicrobial resistance in the RICU is vital to enhance infection control practices and reinforce antimicrobial stewardship programs.